Potential study of regenerating waste dialyzer - Maryani, Basri (2014)
The purpose of this study is to characterize the malfunctioned Polysulfone membrane dialyzer and to determine the efficiency of dialyzer cleaning solution in regenerating the waste dialyzer. This study was conducted in the Clean Laboratory of FKASA , with the scope of study was limited in regenerating the membrane dialyzer by characterized it by leak of pressure and measure the TCV (Total Cell Volume) of the dialyzer and determining the effect of different concentration of cleaning solution towards the membrane dialyzer. Samples were taken from Islam Makmur Hemodialysis Center. The membrane dialyzer were reprocessed and regenerated by using an Automatic Dialyzer Reprocessor Machine and using AAMI (Association of the Advancement Medical of Instrumentation) standard and recommendation. All the sample dialyzer was characterized using parameters such as TCP (Total Cell Pressure) and TCV (Total Cell Volume). The function of conducted TCP and TCV test is to ensure whether the dialyzer in good condition and to measure the ability of dialyzer to transport solutes, respectively. In the meantime, the dialyzers were also being reprocessed using low and high concentration of dialyzer cleaning solution. The cleaning solution was used is diaclean. As a result, the dialyzer samples have different in TCV reading due to the low and high concentration of cleaning solution tested to the samples. The TCV reading of dialyzer which was tested using low concentration of cleaning solution is smaller whilst the TCV reading for dialyzer that tested using high concentration of cleaning solution is more higher. In conclusion, the used of high concentration of cleaning solution gave positive effect to the efficiency of regenerating membrane dialyzer. Because of that, the kidney patients will be able to undergo treatment in more quality performance.